Spatial Analysis of Vegetation Density Using MSARVI Algorithm and Sentinel-2A Imagery in Ternate City, Indonesia - Rakuasa, Heinrich; Budnikov, Viktor Vladimirovich (Journal of Engineering and Science Application, 2025)
This study aims to analyze vegetation density in Ternate City, Indonesia, using the Modified Soil-Adjusted and Atmospherically Resistant Vegetation Index (MSARVI) algorithm and Sentinel-2A images processed through Google Earth Engine. The analysis results show that the vegetation density index values range from -0.54 to 1.16, with normalization resulting in four density classes: low, medium, dense, and very dense. Ternate Island sub-district had the largest area of very dense vegetation (4,133.12 hectares), while Ternate Tengah sub-district showed the lowest vegetation density, reflecting the significant impact of urbanization. This study revealed that despite anthropogenic pressures, Ternate Island remains an ecologically critical zone. These findings emphasize the importance of conservation efforts and afforestation initiatives to improve environmental resilience amidst the growing challenges of climate change and urban development.